Ore distribution controls of the Navachab Gold Mine, Damara Belt, Karibib District, Namibia - Slabbert, W L (Rhodes University, Faculty of Science, Department of Geology, 2014)
The Navachab Gold mine, an orogenic lode gold deposit, is located in the Karibib region of the Pan-African (ca. 550-500) Damara belt of central Namibia. Gold mineralisation is developed within the steeply NW dipping limb of the Karibib dome. Here, ore envelopes trend along three main orientations: a) trends shallowly towards the NE (the down plunge extent), b) trends sub-vertically in and along the down plunge extent and c) trends sub-horizontally across the down plunge extent. The down plunge extent represents the bulk of the gold mineralisation, hosting the only high grade ores mined at Navachab. As such, past work primarily focused on establishing the controls to the mineralisation observed here. The sub-vertical and sub"“horizontal ore trends are seen as secondary, lower grade, being hosted in the footwall. By cutting pushbacks into the footwall, in an effort to regain access to high grade pit bottom, future gold production almost exclusively relies upon optimally mining these ores. This underlines the importance to investigate and outline the mineralising controls to the secondary ore trends. This study identified the following prevailing quartz vein sets developed within the footwall, set (1) dips shallowly towards the NE (conjugate vein set), (2) steeply towards the NW (bedding parallel veins) and (3) steeply towards the SE (S2 foliation parallel). The NW and SE dipping sets contain high average gold grades, occurring at an infrequent vein density. The NE dipping veins, as a result of occurrence density alone, was highlighted as the dominant gold hosting set. Veining occurred during the late stages of the NW-SE directed, sub-horizontal shortening (D2) event and is associated with top-to-the-NW thrusting and NW-verging folds. Re-Os molybdenite dating from auriferous quartz veins indicates mineralisation occurred at 525-520 Ma. As crustal shortening amplified the Karibib dome, flexural flow developed fractures along bedding planes, providing the control to bedding parallel veins (NW dipping). With continued crustal compression the dome later experienced fold lock up associated with reduced mean rock stress and sub-horizontal extension occurred along the steeply NW dipping limb. Horizontal extensional gashes sucked in fluids to form the shallowly NE dipping conjugate vein set. These features suggest the regional D2 strain as the first-order control to quartz vein development, down plunge and within the footwall ores. To further define the secondary ores, lithological and structural controls were evaluated on a more detailed local scale. With equal amounts of biotite schist and calc-silicate host rock (bulk of the footwall lithology) material analysed, the biotite schist units were found to contain a larger volume amount of quartz veins. The mineralisation incurred is also developed at higher average gold grades compared to that of the calc-silicates, demonstrating biotite schist having the optimal rheology for quartz vein emplacement. Normal faulting and thrusting occurs widespread, at all scale levels, across the footwall. These were primarily observed along bedding foliations and secondly at higher angles cutting across foliation. The study did not constrain the extent of these, but can conclude faulting plays a very prominent role in re-distributing the secondary ores parallel to bedding along sub-vertical trend planes. Great care should be placed in properly modelling these with 3D software such as Leapfrog. The Navachab gold mineralisation came about as a result of convergent and collisional tectonics activating metamorphic dehydration of the crustal metapelites. As these fluids ascended they absorbed gold from the crust, emplaced by either a magmatic or paleo-placer source. The gold enriched hydrothermal fluids amalgamated in large scale 1ste order structures (shearing of the steep NW limb of the Karibib Dome, the Mon Repos Thrust Zone) that acted as primary active fluid path ways. In the case of Navachab the gold enriched fluid fluxed along these pathways while interacting with fluid sinks related to a physical throttle (brittle schist, folding, bedding parallel shears) and/or a chemical trap (marbles). By summarising and detailing the fluid sinks and active fluid pathways identified by this and previous works, it is strongly recommended that a mineral approach system be designed and implemented as targeting model to lead future exploration endeavours.
Keywords: Gold ores -- Namibia; Ore deposits -- Namibia